Peran dan Kendala Jurnalis dalam Pemberitaan Deforestasi di Aceh: (Studi Terhadap Wartawan Harian Serambi Indonesia Tahun 2019) - Syukri Syamaun (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2021)
This illegal logging practice occurs in almost all districts in Aceh. The mass media should be part of the socialization of various illegal logging cases that have occurred in Aceh. News Serambi Indonesia is able to carry out an in-depth and comprehensive investigation of illegal logging in Aceh. Serambi Indonesia must be able to expose the involvement of the "big and important" figures who played in this case. The questions that will be answered in this research are Why does Serambi Indonesia Daily not report the issues of illegal logging in Aceh comprehensively and thoroughly? What are the problems and obstacles faced by the journalists of the Serambi Indonesia Daily in reporting on the issues of illegal logging in Aceh? The study used a qualitative approach with qualitative descriptive methods with data collection instruments carried out through interviews with journalists who had reported on illegal logging cases in Aceh. The coverage of illegal logging issues in the Serambi Indonesia Daily does not seem to have high news values. The value of the news in question is hardly interesting to follow because the news that is presented is never finished. The journalists of the Serambi Indonesia Daily are constrained by various things in covering and reporting on illegal logging in Aceh